Technology enabled crime: examining the role of cryptocurrency = Technologiegestützte Kriminalität - zur Rolle von Kryptowährungen - McCord, Alex (Kriminologie - das Online-Journal, 2022)
The illicit use of cryptocurrencies is an area in which a race exists between criminals seeking to exploit evolving technology, investigators trying to detect or disrupt activity, and legislators attempting to regulate its use. Law enforcement face multiple challenges, including the identification of offenders and the lack of a consistent regulatory framework to prosecute criminal activity as well as of tools and training to prevent or disrupt crime. To better understand the relationship between cryptocurrency offending and digital disruption* investigation and prevention methods, a review of the existing scientific evidence was conducted with the aim of supporting practitioners, such as the police, in their work of preventing, disrupting and reducing crime. Findings detail the categories and volume of criminal activity as well as the influence of cryptocurrency markets on crime and important aspects for law enforcement practitioners, while a selection of digital disruption investigation and prevention methods proposed by academic security researchers were also identified; these are discussed with recommendations for further research. The influence of criminal activity as a cryptocurrency market driver is additionally considered. It is suggested that criminal use of cryptocurrencies, while increasing in raw numbers, is decreasing by volume relative to the entire market. However, the state of knowledge of the scope, scale and rate of change is uneven between areas of criminal activity, with no consensus as yet on a consistent model of calculation. The paper concludes with a number of recommendations.